Micromolecule modified specific bifunctional coupling photocatalyst as well as preparation method and application thereof

By loading iridium nanoparticles on carbon nitride support and grafting small molecule alcohol amines, a dual-function coupled photocatalyst was developed, which solved the problem of difficulty in coordinating CO2 adsorption activation and mass supply, and achieved high efficiency and stability of the CO2 reduction process sex.

CN119425785APending Publication Date: 2025-02-14NANJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411580898.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively coordinate the adsorption activation and proton supply of CO2, resulting in inefficient CO2 reduction process.

Method used

A small molecule modification specific dual-function coupled photocatalyst is used to integrate CO2 adsorption and mass supply functions by supporting iridium nanoparticles on a carbon nitride support and grafting small molecule alcohol amines.

Benefits of technology

It significantly improves the adsorption capacity and mass supply efficiency of CO2, optimizes the catalytic reaction path, improves the reaction efficiency, and maintains the high activity and good regeneration ability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425785A_ABST
    Figure CN119425785A_ABST
Patent Text Reader

Abstract

The invention discloses a small molecule modified specific bifunctional coupling photocatalyst and a preparation method and application thereof, the catalyst takes carbon nitride as a carrier, iridium nanoparticles are loaded into a triazine or heptaazine unit cavity adjacent to the carbon nitride, and the iridium nanoparticles are loaded into the triazine or heptaazine unit cavity adjacent to the carbon nitride. The micromolecular alcohol amine is connected with the terminal amino group on the carbon nitride and the imine group on the skeleton through hydroxyl in the form of intermolecular hydrogen bonds so as to be grafted on the carbon nitride; the preparation method comprises the following steps: (1) dispersing carbon nitride nanosheets and iridium salt in a solvent, fully mixing, drying, and calcining to obtain powder; and (2) adding the powder obtained in the step (1) into a small molecular alcohol amine solution, fully dispersing, then heating for reaction, and finally washing and drying the solid to obtain the difunctional coupling photocatalyst. According to the invention, the iridium nanoparticles and the micromolecular alcohol amine are simultaneously introduced on the carbon nitride carrier, so that CO2 adsorption and proton supply functions are integrated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor photocatalytic materials, and in particular to a small molecule modified specific bifunctional coupling photocatalyst and a preparation method and application thereof. Background Art

[0002] Artificial photosynthesis, which uses inexhaustible solar energy as energy to convert CO2 into high-value-added fuels, provides an effective solution to the energy crisis and environmental effects. CO2 and H2O are two key species in the reduction process. Usually, the linear molecular structure of CO2 needs to be converted into a bent configuration for activation. However, its adsorption on the surface of traditional photocatalysts is usually inefficient. In addition, the hydrogenation step requires a large amount of *H supply, and H2O is the simplest and most economical proton source. However, kinetically, the slow dissociation of H2O significantly hinders the multi-proton coupled electron transfer process, thereby affecting the formation of key intermediates.

[0003] Precise regulation of CO2 adsorption and proton supply is particularly urgent. Current research is often one-sided, focusing mainly on the design of a single function to improve the reaction efficiency of a specific step. For example, some studies focus on improving the adsorption activation capacity of CO2, while others focus on enhancing the dissociation of H2O to facilitate proton supply. Obviously, this single function is not suitable for complex CO2 reduction processes that require the synergy of multiple molecules. In contrast, the development of catalysts with multiple functions can provide greater flexibility for regulating complex multi-electron and multi-reaction pathways, which is expected to significantly improve the overall efficiency of CO2 reduction.

[0004] Although studies have explored the application of bifunctional catalysts in enhancing light absorption, regulating electronic structure and promoting charge separation, there is still a lack of research on how to coordinate CO2 adsorption activation and proton supply by designing bifunctional catalysts. Metal-mediated CO2 adsorption usually relies on weak coordination bonds, which increases the instability of the catalytic process and is easily affected by external environment, thus reducing the catalytic effect. For example, it often fails due to surface poisoning or structural changes. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide a bifunctional coupled photocatalyst integrating CO2 adsorption and proton supply functions; the second purpose of the present invention is to provide a method for preparing the bifunctional coupled photocatalyst; the third purpose of the present invention is to provide the application of the bifunctional coupled photocatalyst in the preparation of CH4 and CO by photocatalytic hydrogenation reduction of CO2 under the assistance of H2O.

[0006] Technical solution: The small molecule modified specific bifunctional coupled photocatalyst described in the present invention uses carbon nitride as a carrier, iridium nanoparticles are loaded into the triazine or heptazine unit cavity of adjacent carbon nitride, and the small molecule alcohol amine is connected to the terminal amino group on the carbon nitride and the imine group on the skeleton through the hydroxyl group in the form of intermolecular hydrogen bonds, thereby being grafted on the carbon nitride.

[0007] Preferably, the small molecule alcohol amine is ethanolamine, propanolamine, butanolamine or 2-amino-1-propanol. With the increase of the carbon chain, the CO2 reduction activity shows a trend of gradually decreasing, and with the increase of the number of branches adjacent to the amino end, the CO2 reduction activity shows a trend of gradually decreasing.

[0008] Preferably, the concentration of the small molecule alcohol amine in the grafting is 0.1 to 1.2 M. As the concentration of the small molecule alcohol amine increases from 0.1 M to 1.2 M, the CO2 reduction activity shows a trend of first increasing and then decreasing.

[0009] Preferably, the content of the iridium nanoparticles in the catalyst is 3-10wt%. When the content of the iridium nanoparticles increases from 3wt% to 10wt%, the CO2 reduction activity shows a trend of first increasing and then decreasing.

[0010] The method for preparing the bifunctional coupled photocatalyst of the present invention comprises the following steps:

[0011] (1) dispersing carbon nitride nanosheets and iridium salt in a solvent, fully mixing, drying, and calcining so that the iridium nanoparticles are loaded into the triazine or heptazine unit cavities of adjacent carbon nitride to obtain a powder;

[0012] (2) adding the powder obtained in step (1) into a small molecule alcohol amine solution, fully dispersing it, and then heating it so that the small molecule alcohol amine is connected to the terminal amino group on the carbon nitride and the imine group on the skeleton in the form of intermolecular hydrogen bonds through the hydroxyl group, and finally washing and drying the solid to obtain the bifunctional coupled photocatalyst.

[0013] Catalyst preparation process Figure 1 As shown, the carbon nitride precursor is taken as an example, and carbon nitride nanosheets are prepared by calcination. Then, iridium nanoparticles are loaded in the cavities of the adjacent heptazine units of the carbon nitride through two-step calcination, and finally ethanolamine is grafted.

[0014] Preferably, in step (1), the carbon nitride precursor is dicyandiamide.

[0015] Preferably, in step (1), the iridium salt is iridium chloride hydrate.

[0016] Preferably, in step (1), the solvent is water.

[0017] Preferably, in step (1), the calcination is a two-step calcination, first calcining at 200-300°C for 4-5h, washing, drying, and then calcining at 500-600°C for 4-5h. Preferably, the heating rate of the calcination process is 2-5°C / min. First, calcining at a lower temperature to achieve controllable anchoring of the metal species, and then calcining at a higher temperature to completely remove the ligand.

[0018] Preferably, in step (2), the heating temperature is 70-100° C. and the heating time is 1.5-5 h.

[0019] Preferably, in step (2), the washing solvent is dimethyl sulfoxide.

[0020] Preferably, the method for preparing the carbon nitride nanosheets comprises the following steps:

[0021] (1) placing dicyandiamide in a covered porcelain boat in a tube furnace at 550-650° C. for 3-4 hours to obtain bulk carbon nitride;

[0022] (2) Grinding the bulk carbon nitride obtained in step (1) into powder, and then calcining at 500-600° C. for 5-6 hours to obtain carbon nitride nanosheets.

[0023] The bifunctional coupled photocatalyst of the present invention is used in the preparation of CH4 and CO by photocatalytic hydrogenation reduction of CO2 under the assistance of H2O.

[0024] Invention Mechanism: The present invention proposes for the first time a small molecule modified specific bifunctional coupled photocatalyst and its preparation method and its application in the photocatalytic hydrogenation reduction of CO2 to CH4 and CO assisted by H2O. The introduction of iridium nanoparticles significantly enhances the activity of H2O, increases the concentration of *H in the local reaction environment, and triggers secondary proton reduction at the interface; the structural characteristics of small molecule alcohol amines give them unique advantages in selectivity and regulation ability, and the adsorption position of CO2 can be precisely controlled through the electronic effect of the group, thereby optimizing the catalytic reaction path. Small molecule alcohol amines form stable CN covalent bonds through the Lewis acid-base interaction between their amino groups and CO2, which not only significantly improves the adsorption capacity of CO2, but also regulates the desorption process of the product through favorable binding kinetics, improves the reaction efficiency, and enables the catalyst to maintain high activity in a variable reaction environment, and exhibits good regeneration ability, and can maintain high catalytic efficiency after multiple uses. In addition, the synergistic effect of iridium nanoparticles and small molecule alcohol amines effectively inhibits the recombination rate of photogenerated electron-hole pairs and improves the carrier mobility.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) by simultaneously introducing iridium nanoparticles and small molecule alcohol amines on a carbon nitride carrier, the CO2 adsorption and proton supply functions are integrated; (2) when the small molecule alcohol amine is ethanolamine, the catalyst has the best effect on catalytic reduction of CO2; (3) when the ethanolamine grafting concentration is 0.8M, the catalyst has the best effect on catalytic reduction of CO2; (4) when the content of iridium nanoparticles is 5wt%, the catalyst has the best effect on catalytic reduction of CO2; (5) the preparation method is simple to operate, low cost, and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The catalyst preparation flow chart of the present invention is as follows;

[0027] Figure 2 a is a transmission electron microscope image of Example 1; Figure 2 b is a high-resolution transmission electron microscopy image of iridium nanoparticles; Figure 2 c is the EDX spectrum of Example 1;

[0028] Figure 3 The performance diagram of photocatalytic reduction of CO2 under simulated sunlight of Example 1 and Comparative Examples 1 to 3;

[0029] Figure 4 The performance diagram of photocatalytic reduction of CO2 in Examples 1 to 3 under simulated sunlight;

[0030] Figure 5 The performance diagram of photocatalytic reduction of CO2 under simulated sunlight of Example 1, Example 4 and Comparative Example 4;

[0031] Figure 6 The performance diagram of photocatalytic reduction of CO2 under simulated sunlight of Example 1 and Examples 5 to 8;

[0032] Figure 7 The performance diagram of photocatalytic reduction of CO2 under simulated sunlight of Example 1 and Examples 9-10;

[0033] Figure 8 The electrochemical impedance diagrams of Example 1 and Comparative Examples 1 to 3 are shown;

[0034] Fig. 9 It is the transient photocurrent response diagram of Example 1 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with embodiments.

[0036] Example 1

[0037] The small molecule modified specific bifunctional coupled photocatalyst of the present invention comprises the following steps:

[0038] (1) Weighing 5 g of dicyandiamide in a covered porcelain boat and placing it in a tube furnace, heating it from room temperature to 550° C. at a heating rate of 3° C. / min, and keeping it at 550° C. for 3 h. After the reaction is completed, naturally cooling it to room temperature to obtain bulk carbon nitride;

[0039] (2) grinding the bulk carbon nitride obtained in step (1) into powder, heating the mixture from room temperature to 500° C. at a heating rate of 5° C. / min, and maintaining the temperature at 500° C. for 5 h to obtain carbon nitride nanosheets;

[0040] (3) Weigh 13 mg of iridium chloride hydrate (i.e., iridium content of 5 wt%) and 100 mg of carbon nitride nanosheets and disperse them in 20 mL of water. After ultrasonication for 10 min, rotary evaporate to dryness and vacuum dry at 80° C.

[0041] (4) calcining the powder obtained in step (3) in an argon flow, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and keeping the temperature at 300° C. for 5 h. After cooling, washing with dimethyl sulfoxide, and vacuum drying at 80° C.;

[0042] (5) calcining the dried powder obtained in step (4) in an argon flow, heating the mixture from room temperature to 550° C. at a heating rate of 2° C. / min, and maintaining the mixture at 550° C. for 5 h;

[0043] (6) After cooling the powder obtained in step (5), add it to 20 mL of 0.8 M ethanolamine solution, continue magnetic stirring, and then ultrasonically treat the mixture for about 30 minutes;

[0044] (7) The suspension obtained in step (6) was then stirred in an oil bath at 70 °C for 3 h. After cooling to room temperature, the treated product was centrifuged and washed with deionized water and dried to obtain the material, which was labeled as M-Ir / ACN.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that a propanolamine solution is used in step (6), and the obtained product is marked as P-Ir / ACN.

[0047] Example 3

[0048] The difference between this example and Example 1 is that a butanolamine solution is used in step (6), and the obtained product is marked as B-Ir / ACN.

[0049] Example 4

[0050] The difference between this example and Example 1 is that 2-amino-1-propanol solution is used in step (6), and the obtained product is labeled as AP-Ir / ACN.

[0051] Example 5

[0052] The present embodiment is different from the embodiment 1 in that the concentration of the ethanolamine solution used in step (6) is 0.1 M, and the obtained product is labeled as 0.1 M-Ir / ACN.

[0053] Example 6

[0054] The present embodiment is different from the embodiment 1 in that the concentration of the ethanolamine solution used in step (6) is 0.2 M, and the obtained product is labeled as 0.2 M-Ir / ACN.

[0055] Example 7

[0056] The present embodiment is different from embodiment 1 in that the concentration of the ethanolamine solution used in step (6) is 0.4 M, and the obtained product is labeled as 0.4 M-Ir / ACN.

[0057] Example 8

[0058] The present embodiment is different from the embodiment 1 in that the concentration of the ethanolamine solution used in step (6) is 1.2 M, and the obtained product is labeled as 1.2 M-Ir / ACN.

[0059] Example 9

[0060] The present embodiment is different from the embodiment 1 in that the mass of the iridium chloride hydrate used in step (3) is 8 mg, that is, the iridium content is 3 wt %, and the obtained product is marked as 3-Ir / ACN.

[0061] Example 10

[0062] The present embodiment is different from the embodiment 1 in that the mass of the iridium chloride hydrate used in step (3) is 25 mg, that is, the iridium content is 10 wt %, and the obtained product is marked as 10-Ir / ACN.

[0063] Comparative Example 1

[0064] The difference between Comparative Example 1 and Example 1 is that no ethanolamine solution is added, that is, steps (6) and (7) are omitted, and the obtained product is marked as Ir / CN.

[0065] Comparative Example 2

[0066] The difference between Comparative Example 2 and Example 1 is that iridium chloride hydrate is not added, that is, steps (3), (4), (5) are omitted, and the obtained product is marked as ACN.

[0067] Comparative Example 3

[0068] The difference between Comparative Example 3 and Example 1 is that no ethanolamine solution and iridium chloride hydrate are added, that is, steps (3)(4)(5)(6)(7) are omitted, and the obtained product is marked as CN.

[0069] Comparative Example 4

[0070] The present embodiment is different from the embodiment 1 in that: the 2-amino-2-methyl-1-propanol solution is used in step (6), and the obtained product is labeled as AMP-Ir / ACN.

[0071] Structural characterization

[0072] The structure of the catalyst prepared in Example 1 was characterized and the results are as follows: Figure 2 shown.

[0073] Transmission electron microscopy can be used to clearly image the microscopic morphology of the prepared materials. Figure 2 a It can be seen that Example 1 (M-Ir / ACN) presents a lamellar stacking morphology. Figure 2 b shows ordered and clear lattice fringe spacing, further proving the presence of iridium metal nanoparticles. The appearance of these fringes is usually related to the regular arrangement of crystals, suggesting the good dispersion and relatively small size of iridium nanoparticles in the material. Figure 2 c Energy dispersive X-ray spectroscopy elemental mapping shows the uniform distribution of C, N, O and Ir elements in Example 1 (M–Ir / ACN).

[0074] Performance Characterization

[0075] The materials obtained in the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 4 were subjected to artificial photosynthesis, i.e., a photocatalytic reduction of CO2 activity experiment was carried out under visible light irradiation. The specific steps are as follows:

[0076] (1) 10 mg of each of the materials in Examples 1 to 10 and Comparative Examples 1 to 4 were weighed and dissolved in 1 mL of anhydrous ethanol, and ultrasonically treated to form a uniform solution;

[0077] (2) The above solution was evenly dispersed in a Petri dish, and then the Petri dish was placed in an oven at 60° C. until the ethanol was completely evaporated;

[0078] (3) Place the dried sample together with the culture dish at the bottom of a custom-made glass reactor, and slowly add 1 mL of deionized water to the sample surface using a syringe to ensure the sample is wet; then apply a quartz glass cover with vacuum resin to seal the reactor to prevent gas leakage;

[0079] (4) The sealed reactor is evacuated to a vacuum and then filled with high-purity CO2 to maintain the system pressure between 70 and 80 kPa;

[0080] (5) Place a 300W xenon lamp on the top of the reactor and adjust the distance between the lamp and the catalyst to ensure that the light power density on the catalyst surface is 100mW cm –2 , using a fully automatic online detector and a gas chromatograph to measure the products in the system.

[0081] (1) Effects of small molecule alcohol amines and iridium nanoparticles on CO2 reduction activity

[0082] The photocatalytic performance of Example 1 (M-Ir / ACN), Comparative Example 1 (Ir / CN), Comparative Example 2 (ACN), and Comparative Example 3 (CN) was compared by quantitatively measuring the CH4 and CO products during the entire photocatalytic reduction of CO2. The test results are shown in Figure 2. Figure 3 shown.

[0083] Depend on Figure 3 It can be seen that Example 1 (M-Ir / ACN: CH4-5.25 μmol g –1 h –1 ,CO–5.89 μmol g –1 h –1 ,H2–10.85 μmol g –1 h –1 ); Comparative Example 1 (Ir / CN:CH4–1.47 μmol g –1 h –1 ,CO–1.73 μmol g –1 h –1 ,H2–7.13 μmol g –1 h –1 ); Comparative Example 2 (ACN:CH4–2.07 μmol g –1 h –1 ,CO–2.96 μmol g –1 h –1 ,H2–2.96 μmol g –1 h –1 ); Comparative Example 3 (CN:CH4–0.47 μmol g –1 h –1 , CO – 0.29 μmol g –1 h –1 ,H2–0.13 μmol g –1 h –1). Compared with Comparative Example 3 (CN), the performance of photocatalytic reduction of CO2 in Example 1 (M-Ir / ACN), Comparative Example 1 (Ir / CN) and Comparative Example 2 (ACN) is significantly improved, and the performance improvement of Example 1 (M-Ir / ACN) is the largest. This phenomenon shows that the synergistic catalytic effect between iridium nanoparticles and ethanolamine molecules plays a key role in the CO2 reduction reaction. Specifically, in the absence of ethanolamine molecules, Ir / CN has little effect on the CO2 reduction activity compared with CN, but under the action of iridium nanoparticles, the activity of water molecules is increased and the *H concentration in the local reaction environment is increased. This increase in concentration enables more protons to be transferred to spatially adjacent *CO2 and triggers the secondary proton reduction effect. The effect of ethanolamine molecules on the CO2 reduction activity is more significant, and the amino group of ethanolamine molecules stably interacts with CO2, thereby enhancing the adsorption and activation of CO2.

[0084] (2) Effect of carbon chain length of small molecule alcohol amines on CO2 reduction activity

[0085] The photocatalytic performance of Example 1 (M-Ir / ACN), Example 2 (P-Ir / ACN) and Example 3 (B-Ir / ACN) was compared by quantitatively measuring the CH4 and CO products during the entire photocatalytic reduction of CO2. The test results are shown in Figure 4 shown.

[0086] Depend on Figure 4 It can be seen that Example 1 (M-Ir / ACN: CH4-5.25 μmol g –1 h –1 ,CO–5.89 μmol g –1 h –1 ,H2–10.85μmol g– 1 h –1 ); Example 2 (P-Ir / ACN:CH4-1.62 μmol g –1 h –1 , CO – 2.96 μmol g –1 h –1 ,H2–6.00 μmol g –1 h –1 ); Example 3 (B-Ir / ACN:CH4-1.85 μmol g –1 h –1 ,CO–1.17 μmol g –1 h –1 ,H2–3.33 μmol g –1 h –1). With the increase of carbon chain from Example 1 (M-Ir / ACN), Example 2 (P-Ir / ACN) to Example 3 (B-Ir / ACN), the CO2 reduction activity showed a trend of gradually decreasing.

[0087] (3) Effect of the number of side chains of small molecule alcohol amines on CO2 reduction activity

[0088] The photocatalytic performance of Example 1 (M-Ir / ACN), Example 4 (AP-Ir / ACN) and Comparative Example 4 (AMP-Ir / ACN) was compared by quantitatively measuring the CH4 and CO products during the entire photocatalytic reduction of CO2. The test results are shown in Figure 5 shown.

[0089] Depend on Figure 5 It can be seen that Example 1 (M-Ir / ACN: CH4-5.25 μmol g –1 h –1 ,CO–5.89 μmol g –1 h –1 ,H2–10.85 μmol g –1 h –1 ); Example 4 (AP-Ir / ACN:CH4-1.45 μmol g –1 h –1 ,CO–1.08 μmol g –1 h –1 ,H2–6.15 μmol g –1 h –1 ); Comparative Example 4 (AMP–Ir / ACN:CH4–0.86 μmol g –1 h –1 ,CO–0.71 μmol g –1 h –1 ,H2–2.98 μmol g –1 h –1 ). As the number of branches adjacent to the amino end increases from Example 1 (M-Ir / ACN), Example 4 (AP-Ir / ACN) to Comparative Example 4 (AMP-Ir / ACN), the CO2 reduction activity shows a trend of gradually decreasing.

[0090] (4) Effect of amine solution concentration on CO2 reduction activity

[0091] The photocatalytic performance of Example 5 (0.1M-Ir / ACN), Example 6 (0.2M-Ir / ACN), Example 7 (0.4M-Ir / ACN), Example 1 (0.8M-Ir / ACN) and Example 8 (1.2M-Ir / ACN) was compared by quantitatively measuring the CH4 and CO products during the entire photocatalytic reduction of CO2. The test results are shown in Figure 6 shown.

[0092] Depend on Figure 6 It can be seen that Example 5 (0.1M-Ir / ACN:CH4-1.52μmol g –1 h –1 ,CO–2.87 μmol g –1 h –1 ,H2–3.26 μmol g –1 h –1 ); Example 6 (0.2M-Ir / ACN:CH4-2.34μmol g –1 h –1 ,CO–3.04 μmol g –1 h –1 , H2 – 4.38 μmol g –1 h –1 ); Example 7 (0.4M-Ir / ACN:CH4-3.82μmol g –1 h –1 ,CO–3.21 μmol g –1 h –1 ,H2–7.28 μmol g –1 h –1 ); Example 1 (M-Ir / ACN, i.e., 0.8M-Ir / ACN: CH4-5.25 μmol g –1 h –1 ,CO–5.89 μmol g –1 h –1 ,H2–10.85 μmol g –1 h –1 ); Example 8 (1.2M-Ir / ACN:CH4-2.37μmol g –1 h –1 ,CO–3.46 μmol g –1 h –1 ,H2–9.12 μmol g –1 h –1). The results show that the concentration of ethanolamine solution affects the CO2 reduction activity. As the concentration of ethanolamine increases from 0.1M to 1.2M, the CO2 reduction activity shows a trend of first increasing and then decreasing. Therefore, there is an optimal ethanolamine concentration range within which the maximum catalytic activity is achieved.

[0093] (4) Effect of iridium nanoparticle content on CO2 reduction activity

[0094] The photocatalytic performance of Example 9 (3-Ir / ACN), Example 1 (5-Ir / ACN) and Example 10 (10-Ir / ACN) was compared by quantitatively measuring the CH4 and CO products during the entire photocatalytic reduction of CO2. The test results are shown in Figure 7 shown.

[0095] Depend on Figure 7 It can be seen that in Example 9 (3–Ir / ACN:CH4–3.14 μmol g –1 h –1 ,CO–4.98 μmol g –1 h –1 ,H2–7.09 μmol g –1 h –1 ); Example 1 (M–Ir / ACN, i.e., 5–Ir / ACN: CH4–5.25 μmol g –1 h –1 ,CO–5.89 μmol g –1 h –1 ,H2–10.85 μmol g –1 h –1 ); Example 10 (10–Ir / ACN:CH4–1.70 μmol g –1 h –1 ,CO–2.60 μmol g –1 h –1 ,H2–7.48 μmol g –1 h –1 ). The results show that the concentration of iridium nanoparticles affects the CO2 reduction activity. There is a critical value for the optimal concentration of iridium nanoparticles, within which the maximum CO2 reduction activity can be achieved. When the content of iridium nanoparticles increases from 3wt% to 10wt%, the CO2 reduction activity shows a trend of first increasing and then decreasing.

[0096] Photoelectric performance

[0097] Electrochemical impedance test and transient photocurrent response were performed on Example 1 and Comparative Examples 1 to 3 using an electrochemical workstation in a standard three-electrode system.

[0098] Test method: 0.1mol / L Na2SO4 aqueous solution was used as electrolyte, Pt wire was used as counter electrode, and Ag / AgCl standard electrode was used as reference electrode. The working electrode was prepared by drop coating method, and the specific operation was as follows: sample (10mg) and nafion (10μL) were dispersed in 1mL ethanol, and after ultrasonic dispersion, 120μL of the mixed solution was dropped on 2cm x 1cm FTO conductive glass, and then the prepared working electrode was dried in an oven at 60℃.

[0099] The photoelectrochemical properties of the prepared samples can be analyzed by electrochemical impedance spectroscopy and transient photocurrent response. Figure 8 and 9 shown.

[0100] Depend on Figure 8 It can be seen that compared with Comparative Example 3 (CN), Example 1 (M-Ir / ACN), Comparative Example 1 (Ir / CN) and Comparative Example 2 (ACN) all showed smaller arc radii in the electrochemical impedance test, which shows that the addition of iridium nanoparticles and ethanolamine effectively reduced the impedance of the catalyst system. Among them, Example 1 (M-Ir / ACN) showed the smallest arc radius, indicating that the synergistic effect of iridium nanoparticles and ethanolamine molecules significantly reduced the carrier transfer resistance of the system.

[0101] Depend on Fig. 9 It can be seen that in terms of transient photocurrent response, compared with Comparative Example 3 (CN), Example 1 (M–Ir / ACN), Comparative Example 1 (Ir / CN) and Comparative Example 2 (ACN) all exhibit higher photocurrent density, and Example 1 (M–Ir / ACN) has the highest photocurrent density.

[0102] Therefore, combined with the results of electrochemical impedance spectroscopy and transient photoelectric response, Example 1 (M-Ir / ACN) exhibits the lowest carrier transfer resistance and the highest transient photocurrent response capability compared to other samples. This result shows that the synergistic effect of iridium nanoparticles and ethanolamine molecules can effectively promote the separation of photogenerated electrons and holes and accelerate the transport and migration of carriers.

Claims

1. A small molecule modified specific bifunctional coupled photocatalyst, characterized in that: Using carbon nitride as a carrier, iridium nanoparticles are loaded into the triazine or heptazine unit cavity of adjacent carbon nitride, and small molecule alcohol amines are connected to the terminal amino group on the carbon nitride and the imine group on the skeleton through hydroxyl groups in the form of intermolecular hydrogen bonds and are thus grafted onto the carbon nitride.

2. The bifunctional coupled photocatalyst according to claim 1, characterized in that: The small molecule alcohol amine is ethanolamine, propanolamine, butanolamine or 2-amino-1-propanol.

3. The bifunctional coupled photocatalyst according to claim 1, characterized in that: The concentration of the small molecule alcohol amine in the grafting is 0.1-1.2M.

4. The bifunctional coupled photocatalyst according to claim 1, characterized in that: The content of the iridium nanoparticles in the catalyst is 3-10 wt%.

5. A method for preparing a bifunctional coupled photocatalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dispersing carbon nitride nanosheets and iridium salt in a solvent, fully mixing, drying, and calcining so that the iridium nanoparticles are loaded into the triazine or heptazine unit cavities of adjacent carbon nitride to obtain a powder; (2) adding the powder obtained in step (1) into a small molecule alcohol amine solution, fully dispersing it, and then heating it so that the small molecule alcohol amine is connected to the terminal amino group on the carbon nitride and the imine group on the skeleton in the form of intermolecular hydrogen bonds through the hydroxyl group, and finally washing and drying the solid to obtain the bifunctional coupled photocatalyst.

6. The method for preparing a bifunctional coupled photocatalyst according to claim 5, characterized in that: In step (2), the heating temperature is 70-100° C. and the heating time is 1.5-5 h.

7. The method for preparing a bifunctional coupled photocatalyst according to claim 5, characterized in that: In step (1), the calcination is a two-step calcination, first calcining at 200-300°C for 4-5 hours, washing and drying, and then calcining at 500-600°C for 4-5 hours.

8. The method for preparing a bifunctional coupled photocatalyst according to claim 5, characterized in that: The washing solvent is dimethyl sulfoxide.

9. The method for preparing a bifunctional coupled photocatalyst according to claim 5, characterized in that: The method for preparing the carbon nitride nanosheets comprises the following steps: (1) placing dicyandiamide in a covered porcelain boat in a tube furnace at 550-650° C. for 3-4 hours to obtain bulk carbon nitride; (2) Grinding the bulk carbon nitride obtained in step (1) into powder, and then calcining at 500-600° C. for 5-6 hours to obtain carbon nitride nanosheets.

10. Use of the bifunctional coupled photocatalyst according to any one of claims 1 to 4 in the preparation of CH4 and CO by photocatalytic hydrogenation reduction of CO2 under the assistance of H2O.